Analysis of Lexical Meaning of Verbs in the Translation of the Article “Media Digitalization and Political Communication” in NADI Magazine Edition 28/2021 - Muhammad Azmi Fahreza; Tanti Kurnia Sari (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The purpose of this study is to describe how the analysis of the lexical meaning of verbs in the translation of the article Digitalization of Media and Political Communication in NADI Magazine Edition 28/2021. This study uses a qualitative descriptive method to analyze the lexical meaning of verbs in Indonesian and German translations. Data were taken from the article "Digitization of Media and Political Communication" in NADI Magazine edition 28/2021 and its translation. Data collection was carried out through document studies involving dictionary analysis to understand the lexical meaning of verbs in both languages. Of the 114 verbs analyzed, 86 (75.43%) had equivalent meanings, 26 (22.80%) had slightly equivalent meanings, and 2 (1.77%) were not equivalent. This study shows that most verbs have equivalent meanings between the source and target languages, although some words experience shifts in meaning. These results emphasize the importance of a deep understanding of lexical meaning in the translation process to ensure equivalence of meaning between languages.